Mudanças globais: avaliando as interações entre CO2, eutrofização e espécies não nativas em ecossistemas aquáticos continentais. - Hein, Gabriela Sponchiado (2022)
Ecosystems respond to the direct, indirect and synergistic effects of global changes caused by human activity. The understanding of the impacts of these changes and especially of the interaction between the impacts is still limited, especially for aquatic environments, because the interaction between them is rarely considered in environmental studies and assessments. We conducted a systematic literature review on the combination of the factors (i) increase of CO2, (ii) eutrophication and (iii) non-native species to verify how these factors have been considered in the context of climate change in freshwater ecosystems studies. Through the Web of Science database, we searched for articles published in English, up to 2020. Following the PRISMA protocol, 62 articles were analyzed. Only 8% of them addressed the combination of the three factors, among them, eutrophication was the most evaluated global change. Still, the studies do not seem to be looking for answers in a broad way and covering several ecological aspects, since they are concentrated in specific regions such as the Netherlands and United States (44%). Studies most focus on one type of environment, the lentic; use organisms from the base of the food-web; apply the experimental approach; evaluate one organizational level (community) and one response variable (biomass). We identified that the effect of the combination of factors is rarely classified with the terms synergistic and antagonist, even when the authors find these patterns. Our main findings reveal that little attention has been given to the combination of factors in freshwater ecosystems. We also find that when interactions are considered, non-native species tend to be favored and algal blooms intensified (74%). Considering that one of the major challenges is to understand how the interaction between global change factors will affect ecosystems, the combinations of factors still need to be prioritized in studies of aquatic ecosystems.